Financial Sector Surveillance and the IMF. - Gola, Carlo (IMF Working Papers., 2009)
The global financial crisis has magnified the role of Financial Sector Surveillance (FSS) in the Fund's activities. This paper surveys the various steps and initiatives through which the Fund has increasingly deepened its involvement in FSS. Overall, this process can be characterized by a preliminary stage and two main phases. The preliminary stage dates back to the 1980s and early 1990s, and was mainly related to the Fund's research and technical assistance activities within the process of monetary and financial deregulation embraced by several member countries. The first ""official"" phase o.